(untitled) (Terr@ Plural, 2023)
The geodiversity can be analyzed based both on its correlation with biodiversity and in relation to its geoconservation strategies, among them, there is the geoculture, which proposes the analysis of the influence that rocks, minerals, fossils, reliefs, geoforms, landscapes, soils and waters had and have on cultural manifestations, material or imaterial. In this context and considering the significant geodiversity of the southern region of Ceará, the Cariri cearense, aiming to contribute to the discussion of the concept of geoculture and, consequently, to the promotion of knowledge and promotion of geodiversity and its components, this article aims to analyze the geodiversity present in the municipal symbolism of Cariri cearense, through the toponymy, anthems and flags of its municipalities. Methodologically, the research was developed based on the concept of geoculture, with activities in the office, with the systematic review of bibliographic, documentary and cartographic surveys, considering the thematic and spatial sections adopted, laboratory and, secondarily, field stages, the results of which were analyzed together. The results show the importance of geodiversity in the context of the official symbols of these municipalities, a considerable part of the regional identity.